NO catalytic oxidation over an ultra-large surface area LaMnO3+δ perovskite synthesized by an acid-etching method. Issue 74 (22nd July 2016) - Zhao, Baohuai; Ran, Rui; Sun, Li; Guo, Xingguo; Wu, Xiaodong; Weng, Duan
Abstract : After etched by acid solution, abundant cationic vacancies appear in A sites of the perovskite structure, leading to a loose structural framework which may contribute the extra surface area, the formation of oxygen vacancies and Mn 4+ . Abstract : The perovskite oxides LaMnO3+ δ were prepared by a citrate method and then etched by acid solution with different times. After etching, the perovskite structures of all the catalysts remained, the surface area enlarged apparently, and the NO catalytic oxidation activities were obviously promoted by increasing the etching time. Long-term experiments revealed the acceptable stability of the etched catalysts. The favorable activities of the etched LaMnO3+ δ catalysts were mainly due to their high specific surface area, abundant activated oxygen species and vacancies, as well as the higher valence state of Mn ions resulting from the loss of La 3+ in the perovskite structure.